BmC-LZM-like2/4 mediates antiviral defense against BmNPV via dorsal pathway - Junming Xia; Yifan Yang; Shigang Fei; Yigui Huang; Jiasheng Lin; Luc Swevers; Min Feng; Jingchen Sun (Pesticide Biochemistry and Physiology, 2026)

Oxytocin Regulated Neuroinflammation through OTR/Mitochondria Mediated Pathway to Improve Hypoxia-Induced Brain Injury - Xiaomei Yang; Kai Li; Lin Chen; Lei Wang; Xuyang Wang; Kangping Lu; Yu Bai; Yonghao Hou; Jingchen Hou; Chao Wang; Xiaoyan Cheng; Joseph Oldam; et al. (Molecular Neurobiology, 2025)

Suppression of TaHDA8-mediated lysine deacetylation of TaAREB3 acts as a drought-adaptive mechanism in wheat root development - Zehui Liu; Qun Yang; Xingbei Liu; Jinpeng Li; Lei Zhang; Wei Chu; Jingchen Lin; Debiao Liu; Danyang Zhao; Xiao Peng; Chaowu Zeng; Mingming Xin; et al. (Molecular Plant, 2025)

Drug-free and non-crosslinked chitosan/hyaluronic acid hybrid hydrogel for synergistic healing of infected diabetic wounds - Yao Lin; Jingchen Xu; Yuanhao Dong; Yue Wang; Chenhao Yu; Yuanhong Li; Chaoliang Zhang; Qianming Chen; Song Chen; Qiang Peng (Carbohydrate Polymers, 2023)

Transcranial Direct-Current Stimulation Regulates MCT1-PPA-PTEN-LONP1 Signaling to Confer Neuroprotection After Rat Cerebral Ischemia–Reperfusion Injury - Xiangyi Kong; Wenjie Hu; Yu Cui; Jingchen Gao; Xujin Yao; Jinyang Ren; Tao Lin; Jiangdong Sun; Yunyi Gao; Xiaohua Li; Hui Wang; Huanting Li; et al. (Molecular Neurobiology, 2022)
Propionic acid (PPA) is a critical metabolite involved in microbial fermentation, which functions to reduce fat production, inhibit inflammation, and reduce serum cholesterol levels. The role of PPA in the context of cerebral ischemia–reperfusion (I/R) injury has yet to be clarified. Increasing evidence indicate that transcranial direct-current stimulation (tDCS) is a safe approach that confers neuroprotection in cerebral ischemia injury. Here, we show that the levels of PPA were reduced in the ischemic brain following a rat cerebral I/R injury and in the cultured rat cortical neurons after oxygen–glucose deprivation (OGD), an in vitro model of ischemic injury. We found that the decreased levels of transporter protein monocarboxylate transporter-1 (MCT1) were responsible for the OGD-induced reduction of PPA. Supplementing PPA reduced ischemia-induced neuronal death after I/R. Moreover, our results revealed that the neuroprotective effect of PPA is mediated through downregulation of phosphatase PTEN and subsequent upregulation of Lon protease 1 (LONP1). We demonstrated that direct-current stimulation (DCS) increased MCT1 expression and PPA level in OGD-insulted neurons, while tDCS decreased the brain infarct volume in the MCAO rats via increasing the levels of MCT1 expression and PPA. This study supports a potential application of tDCS in ischemic stroke.

Research on Roof Cutting and Pressure Releasing Technology of Cumulative Blasting in Deep and High Stress Roadway - Xiaojie Yang; Di Yuan; Haojie Xue; Yubing Gao; Xichun Tian; Jingchen Qi; Lin Hou; Jindong Cao (Geotechnical and Geological Engineering, 2021)

The Effect of Sodium Fluoride on Cell Apoptosis and the Mechanism of Human Lung BEAS-2B Cells In Vitro - Jun Ying; Jie Xu; Liping Shen; Zhijie Mao; Jingchen Liang; Shuangxiang Lin; Xinyan Yu; Ruowang Pan; Chunxia Yan; Shengbin Li; Qiyu Bao; Peizhen Li (Biological Trace Element Research, 2017)